2023
DOI: 10.1111/1467-8578.12454
|View full text |Cite
|
Sign up to set email alerts
|

The 2022 SEND Green Paper and the SENCo: more evidence on demographics, qualifications and leadership status

Abstract: The 2022 Special Educational Needs and Disability (SEND) Review in England has proposed changes to the way in which SENCos are trained before working in English schools. Although the DfE collects data relating to the demographics of all teachers, the 2022 SEND Review Green Paper does not draw on this to support or inform the changes being proposed. A Freedom of Information request was made to the DfE, from which actual data could be acquired, with breakdowns by age, gender, qualifications and leadership status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These include the time allocated to the SENCo for their role (see Boddison et al., 2020) and whether they have enough authority in their school (Dobson, 2019). Another more recent issue, however, is the impact of the SEND reforms (DfE, 2022b) and the discussion on whether an NPQ will provide sufficient overview of enough needs to enable SENCos to deliver effective, evidence‐based training (see Dobson, 2023; Done et al., 2023). Policy makers now need to ensure that the suggested reforms still enable effective forms of CPD that are targeted at key professionals such as SENCos, perhaps with an insistence that ongoing CPD forms a compulsory part of registration after award.…”
Section: Discussionmentioning
confidence: 99%
“…These include the time allocated to the SENCo for their role (see Boddison et al., 2020) and whether they have enough authority in their school (Dobson, 2019). Another more recent issue, however, is the impact of the SEND reforms (DfE, 2022b) and the discussion on whether an NPQ will provide sufficient overview of enough needs to enable SENCos to deliver effective, evidence‐based training (see Dobson, 2023; Done et al., 2023). Policy makers now need to ensure that the suggested reforms still enable effective forms of CPD that are targeted at key professionals such as SENCos, perhaps with an insistence that ongoing CPD forms a compulsory part of registration after award.…”
Section: Discussionmentioning
confidence: 99%
“…The positionality of SENCos within professional hierarchies is concerning. Although it is ten years since policy recommended that SENCos be part of the senior leadership team to provide them with the required time and status to fulfil their complex role, Dobson's (2023) recent research found that just 36% of SENCos are 'senior or strategic' leaders within school settings, and that just over 40% of SENCos do not technically have any leadership responsibilities. This inevitably places strain on SENCos to combine both their teaching and heavily bureaucratised managerial roles.…”
Section: Working With Familiesmentioning
confidence: 99%